Christian Ethics' Understanding of Law on Campus - E.E Aprilita; Kristina Veronika Sianturi (EXOUSIA : Jurnal Pendidikan Agama Kristen, 2022)
As educated people, students are obliged to obey the laws and regulations on campus, especially in the environment of Christian Higher Education which is shaded by the Ministry of Religion and based on the God’s word. Students should set a good example in conducting law on campus as proof that the student is someone who is educated and at the same time has Christian ethics. In reality, there are some students who violate and are indifferent to the laws and regulations on campus. There are still some students who behave inconsistently with ethical and legal moral standards in the campus area. This study aims to examine the correlation of the level of student understanding regarding Christian ethics to the observance of obedience to law in campus. This research was conducted in the campus environment of the Tarutung State Christian Institute, using a sioner cake filled with students. Based on the results of research and data processing, the correlation coefficient obtained is 0.661 (high correlation). The effect of the Christian ethical understanding variable on obedience to the law was 43.8%. Thus, students' understanding of Christian ethics needs to be further improved through seminars or other events related to it.